Kompetensi Manajerial Kepala Madrasah dalam Meningkatkan Mutu Pembelajaran di Madrasah Aliyah An Najah Pati Tahun 2024 - Muhlisin, Muhlisin (Pascasarjana IAIN Kudus, 2024)
Managerial Competence of Madrasah Principal in Improving Learning Quality at Madrasah Aliyah An Najah Pati in 2024. Learning quality is a measure of the quality of the teaching and learning process to achieve educational goals. This study uses a descriptive qualitative approach to examine the role of the madrasah head in improving the quality of learning at Madrasah Aliyah An Najah Pati in the 2023/2024 academic year. The research subjects included the madrasah head, deputy head, teachers, and students. Data were collected through observation, interviews, and documentation, and tested for validity using source triangulation techniques. The results showed that madrasah principals have an important role through conceptual skills, humanitarian skills, and technical skills. Good technical skills from madrasah principals have a positive effect on the quality of learning. Supporting factors include adequate facilities and infrastructure, support from educators and education personnel, and teachers' willingness in lesson planning. However, there are inhibiting factors such as low student input, limited internet network, and lack of teacher skills in information technology. Improving the quality of learning includes planning the learning process, implementing learning by teachers, and assessing learning outcomes to measure students' competency achievement and improve the learning process.Mutu pembelajaran adalah ukuran kualitas proses belajar mengajar untuk mencapai tujuan pendidikan. Penelitian ini menggunakan pendekatan kualitatif deskriptif untuk mengkaji peran kepala madrasah dalam meningkatkan mutu pembelajaran di Madrasah Aliyah An Najah Pati Tahun Pelajaran 2023/2024. Subjek penelitian meliputi kepala madrasah, wakil kepala, guru, dan peserta didik. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi, serta diuji keabsahannya dengan teknik triangulasi sumber. Hasil penelitian menunjukkan bahwa kepala madrasah memiliki peran penting melalui keterampilan konsep, keterampilan kemanusiaan, dan keterampilan teknis. Keterampilan teknis yang baik dari kepala madrasah berpengaruh positif terhadap mutu pembelajaran. Faktor pendukung meliputi sarana dan prasarana yang memadai, dukungan dari pendidik dan tenaga kependidikan, serta kemauan guru dalam perencanaan pembelajaran. Namun, ada faktor penghambat seperti input siswa yang rendah, keterbatasan jaringan internet, dan kurangnya kemampuan guru dalam teknologi informasi. Peningkatan mutu pembelajaran meliputi perencanaan proses pembelajaran, pelaksanaan pembelajaran oleh guru, dan penilaian hasil pembelajaran untuk mengukur pencapaian kompetensi peserta didik serta memperbaiki proses pembelajaran.